Chemkin 기반의 1차원 대향류 확산 화염 모델을 활용한 재순환율 및 수소 함량에 따른 메탄-수소 무화염 연소 특성 해석 연구 - 유지호(Jiho Yu); 박진제(Jinje Park); 이용운(Yongwoon Lee); 홍종섭(Jongsup Hong); 이영재(Youngjae Lee) (Clean Technology, 28(3), 2022)
The world is striving to transition to a carbon-neutral society. It is expected that using hydrogen instead of hydrocarbon fuel will contribute to this carbon neutrality. However, there is a need for combustion technology that controls the increased NOx emissions caused by hydrogen co-firing. Flameless combustion is one of the alternative technologies that resolves this problem. In this study, a numerical analysis was performed using the 1D opposed-flow diffusion flame model of Chemkin to analyze the characteristics of flameless combustion and the chemical reaction of methane-hydrogen fuel according to its hydrogen content and flue gas recirculation rate. In methane combustion, as the recirculation rate (Kv) increased, the temperature and heat release rate decreased due to an increase in inert gases. Also, increasing Kv from 2 to 3 achieved flameless combustion in which there was no endothermic region of heat release and the region of maximum heat release rate merged into one. In H2 100% at Kv 3, flameless combustion was achieved in terms of heat release, but it was difficult to determine whether flameless combustion was achieved in terms of flame structure. However, since the NOx formation of hydrogen flameless combustion was predicted to be similar to that of methane flameless combustion, complex considerations of flame structure, heat release, and NOx formation are needed to define hydrogen flameless combustion. 세계는 탄소 중립 사회로의 전환을 추진하고 있으며, 탄화수소계 연료를 수소로 대체함으로써 탄소 중립에 대한 기여를 기대할 수 있다. 하지만 수소 연소에 따른 질소산화물을 제어하기 위한 기술이 필요하며, 무화염 연소 기술이 하나의 대안이 될 수 있다. 본 연구는 수소 함량 및 배가스 재순환율에 따른 메탄-수소 연료의 연소 및 반응 특성을 분석하기 위해 Chemkin 기반의 1차원 대향류 확산화염 모델을 이용하여 해석을 수행하였다. 메탄 연소시 재순환율이 2에서 3으로 증가할 때 열방출의 흡열 구간이 없고 최대 열방출률 영역이 하나로 병합되는 무화염 연소가 달성되었다. 재순환율 3의 수소 전소 시 열방출 측면에서 무화염 연소가 달성되었으나, 화염 구조의 측면에서는 무화염 연소 달성 여부의 판단이 어렵다. 하지만 NO 생성량은 메탄 무화염 연소와 비교하여 유사한 수준으로 예측되었기에 수소 무화염 연소를 규정하기 위해서는 화염 구조, 열방출, NOx 생성에 대한 복합적인 고려가 필요하다.